(untitled) (Research, Society and Development, 2023)
This qualitative study aimed to identify the students’ perspectives on the usage of the shadowing technique used to improve their English-speaking skills during one semester. The participants are 16 Ecuadorian pre-service teachers who are enrolled in the Pedagogy of National and Foreign Languages career at Quevedo State Technical University. The data were collected through a questionnaire and analyzed in the light of the grounded theory. The results of the study show that shadowing provides them with a unique opportunity to develop their fluency, pronunciation, and intonation in the target language. Also, the participants considered shadowing to allow for the internalization of linguistic patterns and grammatical structures in a more natural and automatic way. Consequently, this research underscores the significance of discerning students’ viewpoints on the instructional strategies employed in the classroom to tailor them appropriately to each specific context. Additional studies remain essential within the Ecuadorian framework to delve into how students’ views on educators’ teaching techniques impact them, particularly in terms of their emotional responses.